Fenofibrate Reduces the Severity of Neuroretinopathy in a Type 2 Model of Diabetes without Inducing Peroxisome Proliferator-Activated Receptor Alpha-Dependent Retinal Gene Expression - Enright, Jennifer M. (J Clin Med, 2020)
Fenofibrate slows the progression of clinical diabetic retinopathy (DR), but its mechanism of action in the retina remains unclear. Fenofibrate is a known agonist of peroxisome proliferator-activated receptor alpha (PPARα), a transcription factor critical for regulating metabolism, inflammation and oxidative stress. Using a DR mouse model, db/db, we tested the hypothesis that fenofibrate slows early DR progression by activating PPARα in the retina. Relative to healthy littermates, six-month-old db/db mice exhibited elevated serum triglycerides and cholesterol, retinal gliosis, and electroretinography (ERG) changes including reduced b-wave amplitudes and delayed oscillatory potentials. These pathologic changes in the retina were improved by oral fenofibrate. However, fenofibrate did not induce PPARα target gene expression in whole retina or isolated Müller glia. The capacity of the retina to respond to PPARα was further tested by delivering the PPARα agonist GW590735 to the intraperitoneal or intravitreous space in mice carrying the peroxisome proliferator response element (PPRE)-luciferase reporter. We observed strong induction of the reporter in the liver, but no induction in the retina. In summary, fenofibrate treatment of db/db mice prevents the development of early DR but is not associated with induction of PPARα in the retina.